Humanized mice generated by intra-bone marrow injection of CD133-positive hematopoietic stem cells: application to HIV-1 research - Koma, Takaaki; Odaka, Tokifumi; Lee, Sung-Il; Doi, Naoya; Kondo, Tomoyuki; Okuma, Kazu; Fujisawa, Jun-Ichi; Adachi, Akio; Nomaguchi, Masako (Frontiers in Virology, 2023)
Animal models are essential for basic and clinical research on virus diseases. Humanized mice (mice reconstituted with human hematopoietic cells) have been effectively used for various virus studies as small animal models. Studies on human-tropic HIV-1 have also been performed using different humanized mouse models. Various humanized mice have been generated using distinct mouse strains and engraftment methods. These different techniques affect the reconstitution of human hematopoietic cells in individual mice, and in turn the HIV-1 replication in vivo. In this report, we describe the details of the generation method of humanized mice, i.e., severely immunodeficient mice (NSG mice) transplanted with human CD133-positive cells via intra-bone marrow injection (IBMI). It has been shown that the CD133-positive cells are highly capable to generate CD34-positive cells in vivo and IBMI is an excellent methodology for lymphoid and myeloid cell repopulation. In humanized mice transplanted with CD133-positive cells into the bone marrow, human lymphocytes were increased 3 months after the transplantation and a steady increase in CD4-positive cells was observed until 6–8 months after the transplantation. In order to test the utility of our system, CXCR4-tropic and CCR5-tropic HIV-1 clones were intraperitoneally inoculated into the resultant humanized mice 6–8 months after the transplantation. Upon inoculation at the same dose of viruses, the plasma viral load in CCR5-tropic HIV-1-inoculated mice peaked earlier than that in CXCR4-tropic HIV-1-inoculated mice (2–3 weeks vs 5–10 weeks post-inoculation). While a rapid decrease in CD4-positive cells was observed at the peak or prior to the peak of viremia for CXCR4-tropic HIV-1-inoculated mice, CD4-positive cells were gradually decreased in CCR5-tropic HIV-1-inoculated mice. Upon inoculation at the same dose of viruses, a Nef-deleted R5-tropic HIV-1 exhibited retarded growth kinetics in the inoculated mice compared to the parental virus (around 8 weeks vs 2–3 weeks post-inoculation), which appears to reflect the decrease in replication potential in primary cells. Taken all together, in addition to the humanized mice reported so far, our humanized mice generated by transplanting CD133-positive cells with the IBMI method would be an appropriate prototype model for understanding HIV-1 biology in vivo.